Karakteristik Demografi dan Radiologi Pada Pasien Stroke Hemoragik - Lumbantobing, Lamhot Asnir; Lopez, Claudia da; Nathaniel, Fernando; Wijaya, Dean Ascha (Jurnal Ners, 2024)
Hemorrhagic stroke is bleeding within the brain that occurs due to the rupture of blood vessels. Early diagnosis and prompt management are crucial to prevent rapid neurological deterioration or dysfunction caused by hemorrhagic stroke. This cross-sectional study aims to understand the clinical and radiological characteristics of patients with hemorrhagic stroke at HP Hospital , selected based on specific criteria using total sampling from medical records during the period from December 2022 to July 2023. The variables used in this study are gender, lesion location, Glasgow Coma Scale (GCS), and basic blood laboratory findings. Data are presented in descriptive form. Out of 22 respondents, the mean age was 58.68 years, and it was predominantly female (54.5%). The most common cases are intraventricular hemorrhagic (31.8%). 31.8% of respondents’ level of consciousness were alert and soporous states, respectively. Hypertension was found to be a concomittant dosesase in 90.9% of the respondents. 11 (50%) respondents passed away after receiving treatment. The respondents' laboratory results showed hypokalemia and leukocytosis, with average values of sodium, chloride, hemoglobin, hematocrit, and platelets within normal limits.